Women entrepreneurship: effect of social capital, innovation and market knowledge (2017)
Women entrepreneurship plays a key role in the economic  growth.  This study investigates the mediatory role of innovation concerning  the effect of social capital on entrepreneurship.  The sample  population included 130 female entrepreneurs  in Ilam province, Iran. Using questionnaire  as the main means of data collection, the correlation among variables of entrepreneurship,  innovation, social capital and market knowledge was evaluated. Data analysis was performed  by structural   equation  modeling  in LISREL software.  The findings showed that social capital and innovation had a positive and significant effect on entrepreneurship. However, the impact of social capital on innovation was not confirmed.